Industrial Neuroscience in Aviation Evaluation of Mental States in Aviation Personnel - Borghini, Gianluca; Aricò, Pietro; Di Flumeri, Gianluca; Babiloni, Fabio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book discusses the emerging field of industrial neuroscience, and reports on the authors' cutting-edge findings in the evaluation of mental states, including mental workload, cognitive control and training of personnel involved either in the piloting of aircraft and helicopters, or in managing air traffic. It encompasses neuroimaging and cognitive psychology techniques and shows how they have been successfully applied in the evaluation of human performance and human-machine interactions, and to guarantee a proper level of safety in such operational contexts. With an introduction to the most relevant concepts of neuroscience, neurophysiological techniques, simulators and case studies in aviation environments, it is a must-have for both students and scientists in the field of aeronautic and biomedical engineering, as well as for various professionals in the aviation world. This is the first book to intensively apply neurosciences to the evaluation of human factors and mental statesin aviation.
From the Content: Introduction -- Preliminary Concepts -- Mental States in Aviation.
Keywords: Biomedical engineering; Security systems; Psychology, Experimental; Neurosciences; Aerospace engineering; Astronautics; Biomedical Engineering and Bioengineering; Security Science and Technology; Experimental Psychology; Neuroscience; Aerospace Technology and Astronautics